ANALISIS STRATEGI KOMUNIKASI PIMPINAN LPPM UNHAS TERHADAP KINERJA PEGAWAI - Judith Wira Satya Ambara; Muh Iqbal Sultan; Tuty Bahfiarti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research aims to analyze the communication strategy of the LPPM Unhas leaders on the quality of employee performance. The method used was descriptive with a qualitative approach and field research. Data collection used in-depth interviews, observations, and document studies. Data analysis used descriptive qualitative. The data analysis used analytical techniques according to Miles and Huberman, which consisted of data reduction, presentation, and concluding. The data validity was conducted using the data triangulation technique. The results showed that the analysis of the communication strategy of the UNHAS LPPM leaders on the quality of employee performance included several stages; Having disciplinary rules for entering working hours on time, being together, setting an example for all employees, creating a conducive atmosphere with kinship to employees, improving employee welfare, providing motivation to employees through coaching, and a religious approach. Facts that the method used was organizational information theory which discussed the importance of disseminating information in organizations to maintain the survival of the organization, namely the Hasanuddin University Research and Community Service Institute.